Radiguet Revisited - Leon S. Roudiez (Studies in 20th & 21st Century Literature, 1985)
A re-examination of Raymond Radiguet's novel, Le Diable au corps, from a textual point of view. Thanks to the knowledge made available by linguistic and psychoanalytic theories, we are now able to read this novel less as a study of adolescent love in its more or less universal aspects and more as the account of the destructive behavior of a troubled, narcissistic adolescent who is basically incapable of love. History is brought in only to show that, contrary to appearances, the story is set outside of history. Narrative, word, and letter patterns, in addition to symbolism, are used to justify that interpretation. On the other hand, no attempt is made to "psychoanalyze" Radiguet himself: the text alone is allowed to reveal what the writing subject is doing—regardless of the conscious or unconscious aspect of the "author's" personality.
Keywords: Raymond Radiguet; Le Diable au corps; linguistic; psychoanalytic; theories; adolescent love; destructive behavior; narcissistic; adolescent; outside of history; history; narrative; symbolism; word; letter pattern; psychoanalyze; authorial intent